Effect of Weed Management Practices on Weed Dynamics, Yield Attributes and Yield of Maize - Kantwa, Suman; Jadon, C. K.; Tetarwal, J. P.; Ram, Baldev; Kantwa, S. R.; Yadav, R. K. (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted at Research Farm of Agricultural Research Station, Ummedganj, Kota (Agriculture University, Kota), Rajasthan, India during kharif 2019 to find out the most effective herbicide combination for limiting the menace of weeds in maize. Results showed that density of monocot weeds were observed more than dicot weeds during the experimentation. The prominent weeds were Echinochloa colona, Cyperus rotundus, Digera arvensis, Amaranthus viridis, Acalypha indica and Trianthema portulacastrum etc. caused about 58.3% reduction in grain yield as over two hand weeding at 20 and 40 DAS. In general, grassy weeds were better controlled by herbicides than broad leaves weeds. Among herbicides, maximum weed control efficiency (72.18%) was achieved with application of atrazine 500 g a.i. ha-1 (PE) followed bytopramezone 25.2 g a.i. ha-1 at 20-25 DAS (72.18%) which is very close to two hand weeding at 20 and 40 DAS. Furthermore, this treatment also produced higher grain (3496 kg ha-1) and stover yield (6460 kg ha-1) which was at par with atrazine 500 g a.i. ha-1 (PE) followed by tembotrione 120.75 g a.i. ha-1 (20-25 DAS) and atrazine 500 g a.i. ha-1 (PE)+hand weeding 30 DAS with in-situ weeds mulching. Thus, pre-emergence application of atrazine 500 g a.i. ha-1 (PE) followed by topramezone 25.2 g a.i. ha-1 at 20-25 DAS is recommended for better weed control and yield of maize.